Comparison Of Immunogen Designs That Optimize Peptide Coverage: Reply To Fischer et al. - Nickle, David C; Jojic, Nebojsa; Heckerman, David; Kirovski, Darko; Jojic, Vladimir; Rolland, Morgane; Pond, Sergei Kosakovsky; Mullins, James I (PLoS Computational Biology, 2008)
In our paper “Coping with Viral Diversity in HIV Vaccine Design” [1], we presented several approaches to incorporate viral variability within vaccine immunogens, including judicious choice of natural strains. Most of our approaches included at least one collinear gene length corresponding to the Center-of-Tree (COT) sequence, which has near-optimal peptide coverage for a single gene. Inclusion of a COT sequence and optimizing the rest of the immunogen for coverage, as suggested in [2], yielded a construct (COT+) with the greatest coverage of peptide diversity, minimally sacrificing peptide coverage in comparison with unconstrained diversity optimization. Fischer et al. [3] introduced mosaics—a different approach to increasing coverage while maintaining collinearity using an optimization algorithm based on simulated recombination.